ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKADEMIK DI STMIK AMIKOM PURWOKERTO - Giat Karyono (Telematika, 2009)
Academic Information Systems is one of the main functions in a data processing activities of students in Higher Education "STMIK AMIKOM Purwokerto”. This paper contains the results of the analysis and design of academic information system which can be used to facilitate service to students in the academic. This research uses the waterfall development model system. This research produces a design application program to assist academic part in processing the data processing students and lecturers at STMIK AMIKOM Purwokerto so that the institution has an academic information system faster, more efficient, and easy to use